Effects of Light Intensity and Wavelength on the Phototaxis of the Crassostrea gigas (♂) and Crassostrea sikamea (♀) Hybrid Larvae - Zhang, Xuekai; Fan, Chao; Zhang, Xingzhi; Li, Qiongzhen; Li, Yangchun; Wang, Zhaoping (Frontiers in Marine Science, 2021)
Light sensitivity is important for marine benthic invertebrates, and it plays a vital role in the oysters settling. Generally, the emerging of eyespot is a signal of oyster larvae settling, while like most of the other coastal species, the oysters are threatened by artificial light pollution. Crassostrea gigas and Crassostrea sikamea are two oyster species naturally distributed in China, and their hybrids are potential material for oyster cross-breeding. Therefore, we investigated the phototaxis of hybrid eyespot larvae and eyeless larvae under different light intensities and wavelengths to uncover how light affects their behaviors. The results indicated that hybrid oyster larvae had positive phototaxis to specific light intensity and wavelength. We further concluded that 5 lx was the positive phototaxis light intensity for the eyeless hybrid larvae, and that the acceptable light intensity range of the eyespot hybrid larvae expanded to 5–10 lx, but no higher than 15 lx; besides, the hybrid larvae behaved negatively to the light over 25 lx. The present study also suggested the positive effects of green light on larvae gathering and the induction of red light on eyespot larvae settling. In conclusion, our study may contribute to the understanding of phototaxis of hybrid oyster larvae, as well as the further perspective of light pollution on benthic communities and coastal system restoration.